已知x^2+x-6是多项式2x^4+x^3-ax^2+bx+a+b-1的因式,则a=( ),b=( ).
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 04:23:41
已知x^2+x-6是多项式2x^4+x^3-ax^2+bx+a+b-1的因式,则a=( ),b=( ).
已知x^2+x-6是多项式2x^4+x^3-ax^2+bx+a+b-1的因式,则a=( ),b=( ).
已知x^2+x-6是多项式2x^4+x^3-ax^2+bx+a+b-1的因式,则a=( ),b=( ).
设2x^4+x^3-ax^2+bx+a+b-1=M(x^2+x-6)=M(x-2)(x+3)
则当x=2和x=-3时,右边等于0
所以左边也等于0
x=2
2x^4+x^3-ax^2+bx+a+b-1=32+8-4a+2b+a+b-1=0
-3a+3b+39=0
a-b=13 (1)
x=-3
2x^4+x^3-ax^2+bx+a+b-1=162-27-9a-3b+a+b-1=0
-8a-2b+134=0
4a+b=67 (2)
(1)+(2)
5a=80
a=16
b=a-13=3
设2x^4+x^3-ax^2+bx+a+b-1=M(x^2+x-6)=M(x-2)(x+3)
则当x=2和x=-3时,右边等于0
所以左边也等于0
x=2
2x^4+x^3-ax^2+bx+a+b-1=32+8-4a+2b+a+b-1=0
-3a+3b+39=0
a-b=13 (1)
x=-3
2x^4+x^3-ax^2+bx+a+...
全部展开
设2x^4+x^3-ax^2+bx+a+b-1=M(x^2+x-6)=M(x-2)(x+3)
则当x=2和x=-3时,右边等于0
所以左边也等于0
x=2
2x^4+x^3-ax^2+bx+a+b-1=32+8-4a+2b+a+b-1=0
-3a+3b+39=0
a-b=13 (1)
x=-3
2x^4+x^3-ax^2+bx+a+b-1=162-27-9a-3b+a+b-1=0
-8a-2b+134=0
4a+b=67 (2)
(1)+(2)
5a=80
a=16
b=a-13=3
收起